STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM PENGEMBANGAN PROFESIONALISME GURU DI MIN 5 LABUHAN BATU - neliwati, Neliwati; Adolina, Adolina; Hajjatul , Hajjatul Maria Ulfa; Wahyu Nur Ramadhani , Wahyu Nur Ramadhani (Universitas Yudharta Pasuruan, 2022)
This research aims to determine the strategies implemented by school principals in developing teacher professionalism. Teacher professionalism is needed to obtain good quality output. This research is motivated by the importance of education in supporting the nation's future development and developing the potential of students in facing global competition. The type used in this research is a qualitative case study. The data source was obtained from the MIN 5 Labuhan Batu teacher by collecting data through observation, interviews and documents. Data analysis uses qualitative data analysis which follows the Miles and Huberman concept. The results obtained from the principal's leadership strategy in developing teacher professionalism at MIN 5 Labuhan Batu are (1) preparing school planning and development by formulating short-term vision, mission and goals (1 year) and medium-term goals (4 years), (2 ) implementing the school strategy by improving the work discipline of all school members, including students, teaching staff and education staff, both in terms of learning, administration and action, and (3) establishing good cooperation with supervisors, committees, student parents and other institutions. Internal regional government institutions supervision as well as academics asking questions and providing follow-up on school programs.